Plume-lithosphere interactions and LIP-triggered climate crises constrained by the origin of Karoo lamproites - Tappe, Sebastian; Ngwenya, Ntando S.; Stracke, Andreas; Romer, Rolf L.; Glodny, Johannes; Schmitt, Axel Karl (Geochimica et cosmochimica acta, 2023)
We identified a ca. 180 Ma diamondiferous lamproite event in Zambia, establishing a link between ultrapotassic volcanism and the early Jurassic Karoo flood basalt province of sub-Saharan Africa. The cratonic lamproites erupted through the Permo-Triassic Luangwa Rift structure, but MgO-rich ultrapotassic magma formation was unrelated to rifting and triggered by plume-lithosphere interactions during the Karoo LIP event. Elevated Li-Zn-Ti concentrations in magmatic olivine (up to 18.5 ppm Li at 86-90 mol.% forsterite) and strong Sr-Nd-Hf-Pb isotopic enrichment of the host lamproites (87Sr/86Sr = 0.70701-0.70855, εNd = −10.8 to −10, εHf = −20.3 to −19.1, 206Pb/204Pb = 16.8-17.5) suggest partial melting of phlogopite-metasomatized lithospheric mantle domains, at approximately 180-200 km depth. The mantle-like δ7Li values (+2.8 to +5.7‰) of the most pristine lamproite samples are compatible with source enrichment by asthenosphere-derived melts, without significant involvement of recycled sedimentary components. This geochemical fingerprint stands in sharp contrast to the negative δ7Li compositions of primitive K-rich volcanic rocks from collision zone settings, where the shallow mantle sources contain recycled sediment. Isotope modelling demonstrates that the sub-Saharan lamproites originate from a MARID-style metasomatized peridotitic mantle source that underwent incompatible element enrichment at ca. 1 Ga, during tectonic activity associated with Rodinia supercontinent formation. Plume-sourced basaltic and picritic magmas of the 180 Ma Karoo LIP interacted with such K-rich hydrous lithospheric mantle domains, thereby attaining enriched incompatible element and radiogenic isotope compositions. Nd-Hf isotope mass balance suggests that up to 25% of MARID-sourced lamproite melt component contributed to some of the high-Ti flood volcanic units. Although large quantities of volatiles can be transferred from Earth’s mantle to the atmosphere via plume-lithosphere interactions, it is unlikely that outgassing of mantle-sourced sulphur can exceed the climatic impact caused by the release of much more abundant carbon from thick continental roots. Thus, the excess SO2 required to account for transient atmospheric cooling during the early Jurassic, coincident with the Karoo LIP event, must have had a thermogenic origin near the surface of Earth.
Online verfügbar 20. April 2023, Artikelversion 27. April 2023
Gesehen am 05.07.2023